Transferred, Ultrathin Oxide Bilayers as Biofluid Barriers for Flexible Electronic Implants. (20th July 2017) - Song, Enming; Lee, Yoon Kyeung; Li, Rui; Li, Jinghua; Jin, Xin; Yu, Ki Jun; Xie, Zhaoqian; Fang, Hui; Zhong, Yiding; Du, Haina; Zhang, Jize; Fang, Guanhua; et al.
Abstract: The work presented here introduces a materials strategy that involves physically transferred, ultrathin layers of silicon dioxide (SiO2 ) thermally grown on silicon wafers and then coated with hafnium oxide (HfO2 ) by atomic layer deposition, as barriers that satisfy requirements for even the most challenging flexible electronic devices. Materials and physics aspects of hydrolysis and ionic transport associated with such bilayers define their performance and reliability characteristics. Systematic experimental studies and reactive diffusion modeling suggest that the HfO2 film, even with some density of pinholes, slows dissolution of the underlying SiO2 by orders of magnitude, independent of the concentration of ions in the surrounding biofluids. Accelerated tests that involve immersion in phosphate‐buffered saline solution at a pH of 7.4 and under a constant electrical bias demonstrate that this bilayer barrier can also obstruct the transport of ions that would otherwise cause drifts in the operation of the electronics. Theoretical drift–diffusion modeling defines the coupling of dissolution and ion diffusion, including their effects on device lifetime. Demonstrations of such barriers with passive and active components in thin, flexible electronic test structures highlight the potential advantages for wide applications in chronic biointegrated devices. Abstract : Ultrathin, transferred oxide bilayers that are impermeable to both water and ions serve as compatible biointerfaces and robust biofluid barriers with multidecade lifetimes. An optimized strategy exploits a hafnium oxide layer formed by atomic layer deposition on a thermal silicon dioxide layer, both on top of flexible electronics. The findings offer relevance to diverse ranges of biointegrated implantable devices.